Eu-doped CdS nanocrystals synthesized using A. indica: A green route to tailored optical properties for photonic and optoelectronic devices - Sapana Soni; Kusumanjali Deshmukh; Jagjeet Kaur Saluja; Renu Kumari; Mimi Akash Pateria; Mohan L. Verma (Next Nanotechnology)
Europium-doped CdS nanocrystalline thin films were prepared through green synthesis employing A. indica (neem) extracts as a natural capping and reducing agent. Hexagonal wurtzite structure was validated by XRD, with lattice expansion and unit cell volume increase from 1632.62 Å³ (p-CdS) to 8863.03 Å³ (CdS: Eu). UV–Vis spectroscopy showed a redshift in band gap from 3.3 eV (pristine CdS) to 2.2 eV (CdS: 0.05 M Eu), suggesting modification in band structure by Eu doping. PL spectra indicated intense Eu³ ⁺ emissions at 616–620 nm, which were boosted at 0.01 M doping and quenched at elevated concentrations. DFT calculations validated experimental results and partial density of states, indicating Eu-induced 4 f levels in the gap. The cohesive energy (–3.53 eV/atom) established structural stability. This paper presents a green, sustainable synthesis strategy for tuning the optical properties of CdS nanocrystals, and as such, they hold promise for applications in photonic and optoelectronic technology.